2017
DOI: 10.1073/pnas.1714916114
|View full text |Cite
|
Sign up to set email alerts
|

Phytopathogenic fungus hosts a plant virus: A naturally occurring cross-kingdom viral infection

Abstract: The transmission of viral infections between plant and fungal hosts has been suspected to occur, based on phylogenetic and other findings, but has not been directly observed in nature. Here, we report the discovery of a natural infection of the phytopathogenic fungus by a plant virus, cucumber mosaic virus (CMV). The CMV-infected strain was obtained from a potato plant growing in Inner Mongolia Province of China, and CMV infection was stable when this fungal strain was cultured in the laboratory. CMV was horiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
109
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(110 citation statements)
references
References 64 publications
1
109
0
Order By: Relevance
“…Indeed, there are a number of examples of the successful or promising use of mycoviruses to control fungal diseases (37)(38)(39). Interestingly, a number of studies have recently demonstrated that phytopathogenic fungi could be a suitable host of some plant viruses (40)(41)(42), which extends the previously known compatibility of plant viruses and yeast (S. cerevisiae) as hosts (43,44). Conversely, mycoviruses originating from marine fungi (Penicillium aurantiogriseum var.…”
Section: Significancementioning
confidence: 96%
See 1 more Smart Citation
“…Indeed, there are a number of examples of the successful or promising use of mycoviruses to control fungal diseases (37)(38)(39). Interestingly, a number of studies have recently demonstrated that phytopathogenic fungi could be a suitable host of some plant viruses (40)(41)(42), which extends the previously known compatibility of plant viruses and yeast (S. cerevisiae) as hosts (43,44). Conversely, mycoviruses originating from marine fungi (Penicillium aurantiogriseum var.…”
Section: Significancementioning
confidence: 96%
“…The finding that plant viroids can infect phytopathogenic fungi raises the question of whether viroids could be horizontally transferred from the plant to fungus during colonization of plant tissue by the fungal pathogens. In fact, under laboratory conditions, we have previously demonstrated the transfer of a plant RNA virus from the plant to fungus, an event that possibly occurs in natural settings (42). To explore this possibility, we inoculated viroid-free wild-type and Δdcl2 mutant strains of F. graminearum to HSVd-infected N. benthamiana plants.…”
Section: Viroids Could Be Bidirectionally Transferred Between Plants Andmentioning
confidence: 99%
“…Valsa mali but not C. parasitica , and F. graminearum [59] . Due to the close contact between phytopathogenic fungi and plants a change in host range of a tobamo-like virus is plausible.…”
Section: Acidomyces Richmondensis Tobamo-like Virus 1 (Artlv1)mentioning
confidence: 84%
“…Uromyces potyvirus A and Zymoseptoria comovirus A showed strong similarity to other viruses from plants, indicating that both fungi transmit plant viruses that infect both fungi and plants. Fungal transmission of a plant virus has been reported (41). Moreover, plants are known hosts for viruses in the family Virgaviridae , which were also identified in fungi, suggesting that fungi could be alternative hosts.…”
Section: Discussionmentioning
confidence: 99%